2019
DOI: 10.1371/journal.pone.0211730
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping of grain yield in a diverse collection of spring wheat (Triticum aestivum L.) evaluated in southern Australia

Abstract: Wheat landraces, wild relatives and other ‘exotic’ accessions are important sources of new favorable alleles. The use of those exotic alleles is facilitated by having access to information on the association of specific genomic regions with desirable traits. Here, we conducted a genome-wide association study (GWAS) using a wheat panel that includes landraces, synthetic hexaploids and other exotic wheat accessions to identify loci that contribute to increases in grain yield in southern Australia. The 568 access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 46 publications
(64 reference statements)
7
56
0
Order By: Relevance
“…Three of the genomic regions, located on chromosome 4A, 6B, and 7B, were associated with grain weight for the heat response under drought, harvest index, biomass, screenings, and leaf water potential. QTL for grain weight under single and combined drought and heat stress colocated with the QTL on chromosomes 6B and 7B (Valluru et al, 2017;Garcia et al, 2019;Qaseem et al, 2019) and QTL for harvest index and biomass were previously found under heat conditions on chromosome 7B (Qaseem et al, 2019). Using two QTL were reported, mainly wheat accessions from China, for grain number at all three regions (Shi et al, 2017;Sun et al, 2017).…”
Section: Stable Qtl For Yield and Yield Componentsmentioning
confidence: 84%
See 3 more Smart Citations
“…Three of the genomic regions, located on chromosome 4A, 6B, and 7B, were associated with grain weight for the heat response under drought, harvest index, biomass, screenings, and leaf water potential. QTL for grain weight under single and combined drought and heat stress colocated with the QTL on chromosomes 6B and 7B (Valluru et al, 2017;Garcia et al, 2019;Qaseem et al, 2019) and QTL for harvest index and biomass were previously found under heat conditions on chromosome 7B (Qaseem et al, 2019). Using two QTL were reported, mainly wheat accessions from China, for grain number at all three regions (Shi et al, 2017;Sun et al, 2017).…”
Section: Stable Qtl For Yield and Yield Componentsmentioning
confidence: 84%
“…Six other QTL associated with grain weight were detected under well-watered, rainfed, or heat conditions Valluru et al, 2017;Wang et al, 2017;Qaseem et al, 2018) and coincided with the QTL for grain weight under DH and the heat response under drought on chromosome 3B, 5B, and the long arm of chromosome 6B (QGWp.adh-3B.1, QGWp.adh-3B.2, QGWp.adh-5B, QGWt.ara-6B.7, QGWp.ara-6B.3). The QTL on the long arm of chromosome 6B also co-located with QTL for harvest index under combined drought and heat stress (Garcia et al, 2019) as well as single grain weight and leaf chlorophyll content under heat (Shirdelmoghanloo et al, 2016). Regions on chromosome 3B co-located with QTL for tiller number under combined drought and heat stress, grain number, biomass, and harvest index under well-watered conditions (Qaseem et al, 2018), while the region on chromosome 7A coincided with QTL for spike length and water-soluble carbohydrates (Gao et al, 2015;Dong et al, 2016;Sun et al, 2017).…”
Section: Novel Qtl For Drought and Heat Tolerancementioning
confidence: 93%
See 2 more Smart Citations
“…Grain yield is a complex trait controlled mainly by many loci with small effects [1113] and this makes yield more difficult to examine than disease resistance. Improvement in grain yield, however, remains the prime emphasis of many wheat breeding programs [14], and with that, it is necessary to measure gains achieved through different breeding and selection strategies.…”
Section: Introductionmentioning
confidence: 99%